Analysis of High Frequency and Low Frequency Charging Systems on 12VDC Solar Power System Batteries - Firmansyah, Deni; Tharo, Zuraidah (Science Tech Group, 2025)
Batteries are an essential product for alternative energy, required for various electronic devices and everyday human needs. Rechargeable batteries must be carefully managed to avoid quick damage due to improper charging systems or poor-quality chargers. Charging a 12V battery is done by continuously flowing current until the battery voltage reaches its specified value. As technology advances, many battery chargers are available on the market, using either high or low frequencies. By comparing the measurement results of high-frequency charging systems (using MOSFET and switching) and low-frequency systems (using transformers), we can draw conclusions that demonstrate the performance and quality of charging in these different systems.